A review on bovine hydroxyapatite; extraction and characterization. (17th December 2021) - Moradi, Ali; Pakizeh, Majid; Ghassemi, Toktam
Abstract: High rate of bone grafting surgeries emphasizes the need for optimal bone substitutes. Biomaterials mimicking the interconnected porous structure of the original bone with osteoconductive and osteoinductive capabilities have long been considered. Hydroxyapatite (HA), as the main inorganic part of natural bone, has exhibited excellent regenerative properties in bone tissue engineering. This manuscript reviews the HA extraction methods from bovine bone, as one of the principal biosources. Essential points in the extraction process have also been highlighted. Characterization of the produced HA through gold standard methods such as XRD, FTIR, electron microscopies (SEM and TEM), mechanical/thermodynamic tests, and bioactivity analysis has been explained in detail. Finally, future perspectives for development of HA constructs are mentioned.